Mortality of Globitermes sulphureus (family: termitidae) against Gliricidia sepium (family: fabaceae) - Fauziah Abdullah,; Mohd Shukri Mohd Sabri,; Davindran Rajandram, (Pusat Sistematik Serangga ,UKM, 2015)
The mortality of Globitermes sulphureus against essential oil Gliricidia sepium was investigated. High mortality was shown by hexane extract compared to methanolic extract and DCM extract. 50% mortality was achieved after 15 hours exposure towards 2.96 μg/ml (LD50) of G. sepium. neophytadine and coumarine are the compounds that cause mortality to termites.